Efficient solvers for incompressible flow problems: an algorithmic and computational approach - Turek, Stefan (Springer, 1999)
This book discusses recent numerical and algorithmic tools for the solution of certain flow problems arising in Computational Fluid Dynamics (CFD), which are governed by the incompressible Navier-Stokes equations. It contains several of the latest results for the numerical solution of (complex) flow problems on modern computer platforms. Particular emphasis is put on the solution process of the resulting high dimensional discrete systems of equations which is often neglected in other works. Together with the included CD ROM which contains the complete FEATFLOW 1.1 software and parts of the "Virtual Album of Fluid Motion", which is a "Movie Gallery" with lots of MPED videos, the interested reader is enabled to perform his own numerical simulations or he may find numerous suggestions for improving his own computational simulations